ISLAMIC BUSINESS ETHICS, MARKETING STRATEGY, AND INSTITUTIONAL INDEPENDENCE IN ISLAMIC BANKING: A CASE STUDY OF BANK SUMUT SYARIAH KISARAN BRANCH - Khairiyah Fikri Azzahra; Juliana Putri (STAI ALHIKMAH Jakarta, 2026)
AbstractThis study aims to analyze the implementation of Islamic business ethics in marketing strategies at Bank Sumut Syariah Kisaran Branch and examine its contribution to customer trust, perceived transparency, loyalty tendencies, and potential institutional independence. Using a qualitative case study design, data were collected through observation, semi-structured interviews, and documentation, then analyzed thematically. The findings show that honesty (shiddiq), trustworthiness (amanah), and transparency are reflected in financing service practices, particularly in the accurate delivery of product information, protection of customer data, assistance during the financing process, and openness in explaining contracts, costs, payment schemes, obligations, and risks. These ethical practices contribute to customer trust, perceived transparency, satisfaction, and loyalty tendencies, including the willingness to reuse services and recommend them to others. However, this study does not directly measure financial indicators such as third-party fund stability, financing growth, or asset quality. Institutional independence is therefore understood as a potential long-term implication of ethical service relationships and relational capital. Future research should employ quantitative or mixed-methods approaches to test these relationships more comprehensively across broader Islamic banking contexts and institutional performance indicators. ABSTRAKPenelitian ini bertujuan menganalisis implementasi etika bisnis Islam dalam strategi pemasaran di Bank Sumut Syariah Cabang Kisaran serta mengkaji kontribusinya terhadap kepercayaan nasabah, persepsi transparansi, kecenderungan loyalitas, dan potensi kemandirian institusi. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus. Data dikumpulkan melalui observasi, wawancara semi-terstruktur, dan dokumentasi, kemudian dianalisis secara tematik. Temuan menunjukkan bahwa nilai kejujuran (shiddiq), amanah, dan transparansi tercermin dalam praktik layanan pembiayaan, terutama melalui penyampaian informasi produk secara akurat, perlindungan data nasabah, pendampingan proses pembiayaan, serta keterbukaan dalam menjelaskan akad, biaya, skema pembayaran, kewajiban, dan risiko. Praktik etis tersebut berkontribusi terhadap kepercayaan nasabah, persepsi transparansi, kepuasan, dan kecenderungan loyalitas, termasuk kesediaan menggunakan kembali layanan dan merekomendasikannya kepada pihak lain. Namun, penelitian ini tidak mengukur indikator keuangan seperti stabilitas dana pihak ketiga, pertumbuhan pembiayaan, atau kualitas aset. Kemandirian institusi dipahami sebagai implikasi jangka panjang yang potensial dari hubungan pelayanan etis dan modal relasional. Penelitian selanjutnya disarankan menggunakan pendekatan kuantitatif atau metode campuran agar hubungan antara etika bisnis Islam, loyalitas nasabah, kinerja keuangan, dan kemandirian institusi dapat diuji secara lebih menyeluruh dan generalizable pada konteks perbankan syariah Indonesia.K